Development of a radial distribution system analysis tool - Gumera, Vida Joan G.
A Radial Distribution Analysis Tool is developed using Qt Toolkit 4.3.2 Open Source Edition. The computational capabilities of this software include Power Flow, Short Circuit Analysis, optimum Capacitor Placement, and Reliability Calculations. The programs are integrated into one software through a graphical user interface. The power flow program that was already implemented made use of the Backward-Forward Sweep method. The capacitor placement program used genetic algorithm. The short circuit program was implemented using unbalanced phase domain formulation. This software is limited to radial distribution systems only.